The O. Henry Awards Prize Stories, 2001 - Dark, Larry (New York : Doubleday, 2001)
This annual collection consistently brings together the best short fiction published in North American magazines.
The deep / Mary Swan -- Big me / Dan Chaon -- Floating bridge / Alice Munro -- That winter / Fred G. Leebron -- The love of my life / T. Coraghessan Boyle -- The girl with the blackened eye / Joyce Carol Oates -- The smoker / David Schickler -- Female trouble / Antonya Nelson -- The mourning door / Elizabeth Graver -- Zog-19: a scientific romance / Pinckney Benedict -- At the Jim Bridger / Ron Carlson -- Revival road / Louise Erdrich -- The paperhanger / William Gay -- Bliss / Dale Peck -- Bow down / Murad Kalam -- Pastoralia / George Saunders -- Servants of the map / Andrea Barrett.
"An Anchor original"--Title page verso.
O. Henry Memorial Award, 2001.
Keywords: Short stories, American